2022
DOI: 10.3389/fneur.2022.782880
|View full text |Cite
|
Sign up to set email alerts
|

SEEG in 3D: Interictal Source Localization From Intracerebral Recordings

Abstract: BackgroundStereo-electroencephalography (SEEG) uses a three-dimensional configuration of depth electrodes to localize epileptiform activity, but traditional analysis of SEEG is spatially restricted to the point locations of the electrode contacts. Interpolation of brain activity between contacts might allow for three-dimensional representation of epileptiform activity and avoid pitfalls of SEEG interpretation.ObjectiveThe goal of this study was to validate SEEG-based interictal source localization and assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…This was done by evaluating the implantation, and its ability to record an SOZ which fits certain priors on focality and presence of interictal markers of epileptogenicity. Previous studies have only attempted to refine the localization of the epileptic focus 13 , 28 , or aimed to find spiking regions or SOZ missed by the SEEG 14 , 17 19 . Although finding novel spiking regions is a valuable tool to study the interictal network of spikes, they are also known to delineate the irritative zone, which encompasses a larger region than the EZ 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was done by evaluating the implantation, and its ability to record an SOZ which fits certain priors on focality and presence of interictal markers of epileptogenicity. Previous studies have only attempted to refine the localization of the epileptic focus 13 , 28 , or aimed to find spiking regions or SOZ missed by the SEEG 14 , 17 19 . Although finding novel spiking regions is a valuable tool to study the interictal network of spikes, they are also known to delineate the irritative zone, which encompasses a larger region than the EZ 15 .…”
Section: Discussionmentioning
confidence: 99%
“…This might suggest that good EZ coverage is required to observe this flow, but this was not assessed in this work. Other studies have applied electrical source imaging methods on SEEG data to improve the localization of the EZ 17 , or predict surgical outcomes 18 , 19 . They have shown that localizing IEDs or seizures recorded by the SEEG can localize far-field activity not sampled by the SEEG, and using this information, predict surgical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…We defined the onset of an averaged IED as the first 10% of the entire IED, accordingly: either the earliest deflection in the first 7 ms of its rising flank that met the criteria for nonpolyphasic IEDs or the first peak in polyphasic IEDs if the negative amplitude of the highest amplitude of the averaged IED was preceded by an additional amplitude peak (see also Figure 1). 12,27 Half-rise was defined as the midpoint between the onset of the rising flank and the maximum negativity of the averaged IED. 12,27 IED propagation measures the Euclidean distance between the localization of the source maximum at the IED onset and its maximum at the IED peak of the respective inverse method.…”
Section: Definitionsmentioning
confidence: 99%
“…12,27 Half-rise was defined as the midpoint between the onset of the rising flank and the maximum negativity of the averaged IED. 12,27 IED propagation measures the Euclidean distance between the localization of the source maximum at the IED onset and its maximum at the IED peak of the respective inverse method. 12 Colocalization was referred to as concordance by two distinct inverse methods.…”
Section: Definitionsmentioning
confidence: 99%
“…Invasive modalities such as intracranial EEG (iEEG) are considered the gold standard for SOZ identification and have shown excellent accuracy for both adults and pediatric DRE. Stereo-electroencephalography (SEEG) is minimally invasive, uses a three-dimensional configuration of depth electrodes to localize epileptiform activity, and has shown some SOZ identification capability recently (Satzer et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%